2016
DOI: 10.20344/amp.6626
|View full text |Cite
|
Sign up to set email alerts
|

Adult Acne: Prevalence and Portrayal in Primary Healthcare Patients, in the Greater Porto Area, Portugal

Abstract: RESUMOIntrodução: A acne, apesar de caraterística no adolescente, afeta frequentemente o adulto. Em Portugal, não são conhecidos estudos sobre a prevalência da acne no adulto, nomeadamente observada nos grandes centros populacionais. Os objetivos deste estudo foram estimar a prevalência da acne nos utentes dos serviços de cuidados de saúde primários, as suas características, incluindo fatores de risco para início e/ou agravamento, além de coletar informação relacionada com a automedicação e/ou tratamento presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…Other studies have reported a range of acne prevalence from different countries, such as 3.9% in the German population aged between 16 and 70 years 9 and 61.5% in the Portugal population between the ages of 20 and 60 years old. 42 The differences in age range, ethnic background, regions and pollution might explain the difference in the incidence of acne. Skin is the outermost barrier and various air pollutants such as oxides, particulate matter, ultraviolet (UV) radiation, polycyclic aromatic hydrocarbons and the ozone can all affect the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a range of acne prevalence from different countries, such as 3.9% in the German population aged between 16 and 70 years 9 and 61.5% in the Portugal population between the ages of 20 and 60 years old. 42 The differences in age range, ethnic background, regions and pollution might explain the difference in the incidence of acne. Skin is the outermost barrier and various air pollutants such as oxides, particulate matter, ultraviolet (UV) radiation, polycyclic aromatic hydrocarbons and the ozone can all affect the skin.…”
Section: Discussionmentioning
confidence: 99%
“…If relevant, we retrieved the full-text articles. We identified 25 full-text articles, but excluded the following 11 studies: duplicate [ 19 ] (there was a statement in the article by Grossi that it was the same cohort and results as [ 23 ]), beliefs/opinions about acne aggravating food items [ 32 , 33 ], semi-fat/whole milk vs. skim milk/no milk drinkers [ 34 ], Chinese ying-yang medicine [ 35 ], no control group [ 36 ], adult acne (mean age ≥ 30 years) [ 37 , 38 ], milk as part of a Mediterranean diet [ 39 ], milk only as a continuous variable in acne and non-acne groups [ 40 ], and poorly defined intake [ 41 ]. In total, we included 14 studies.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, four cohort studies, 7-9,22 5 case-control, [10][11][12][13]23 and four cross-sectional studies [24][25][26][27] were included into our meta-analysis. The remaining 181 articles were screened for titles and abstracts and 26 articles were considered of interest and full texts were assessed for further evaluation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%